Dual-functional lipid-like nanoparticles for delivery of mRNA and MRI contrast agents. Issue 4 (9th January 2017) - Luo, X.; Li, B.; Zhang, X.; Zhao, W.; Bratasz, A.; Deng, B.; McComb, D. W.; Dong, Y.
Abstract : Lipid-like nanoparticles demonstrate simultaneous delivery of mRNA and MRI contrast agents to express functional proteins and provide real-time visualization. Abstract : Multi-functional nanomaterials possess unique properties, facilitating both therapeutic and diagnostic applications among others. Herein, we developed dual-functional lipid-like nanoparticles for simultaneous delivery of mRNA and magnetic resonance imaging (MRI) contrast agents in order to express functional proteins and provide real-time visualization. TT3-Gd18 LLNs were identified as a lead formulation, which was able to encapsulate 91% of mRNA and 74% of Gd. This formulation showed a comparable or a slightly higher delivery efficiency of mRNA compared to the initial TT3 LLNs. Moreover, a strong MRI signal was observed in the cell pellets treated with TT3-Gd18 LLNs. More importantly, TT3-Gd18 LLNs demonstrated an efficient delivery of mRNA and Gd contrast agents in vivo .